Extracorporeal Membrane Oxygenation Selection by Multidisciplinary Consensus: The ECMO Council. Issue 2 (10th May 2022) - Gannon, Whitney D.; Trindade, Anil J.; Stokes, John W.; Casey, Jonathan D.; Benson, Clayne; Patel, Yatrik J.; Pugh, Meredith E.; Semler, Matthew W.; Bacchetta, Matthew; Rice, Todd W.
Abstract : Coronavirus disease 2019 (COVID-19) has increased the demand for extracorporeal membrane oxygenation (ECMO) and introduced distinct challenges to patient selection for ECMO. Standardized processes for patient selection amidst resource limitations are lacking, and data on ECMO consults are underreported. We retrospectively reviewed consecutive adult ECMO consults for acute respiratory failure received at a single academic medical center from April 1, 2020, to February 28, 2021, and evaluated the implementation of a multidisciplinary selection committee (ECMO Council) and standardized framework for patient selection for ECMO. During the 334-day period, there were 202 total ECMO consults; 174 (86.1%) included a diagnosis of COVID-19. Among all consults, 157 (77.7%) were declined and 41 (20.3%) resulted in the initiation of ECMO. Frequent reasons for decline included the presence of multiple relative contraindications (n = 33), age greater than 60 years (n = 32), and resource limitations (n = 27). The ECMO Council deliberated on every case in which an absolute contraindication was not present (n = 96) via an electronic teleconference platform. Utilizing multidisciplinary consensus together with a standardized process for patient selection in ECMO is feasible during a pandemic and may be reliably exercised over time. Whether such an approach is feasible at other centers remains unknown.